Effect of CCC and Fap on Leaf Diffusive Resistance, Photosynthesis and Respiration in Pearl Millet Under Stress Conditions - Kumari, Santosh; Bharti, S (Annals of Arid Zone, 2016)
Studies conducted in sand culture conditions in screen house on pearl millet (Pennisetum glacum) CV. HH 8-45 revealed that photosynthesis declined and diffusive resistance increased at low leaf water potential. Assimilation ceased at-3.12 MPa at antithesis at -3.52 MPa at grain filling stages. CCC and FAP increased rate of photosynthesis as compared to control at all stages of samplings. Increase in photosynthesis c10scly followed the levels of chlorophyll. soluble protein and moisture contents of the plants. The lowest figures (20.36. 25 and 40.35 sec/cm) for diffusive resistance of adaxial surface were obtained with FAP (0.50 mM) under water stress at vegetative, anthesis and grain-filling stages. Plants treated with CCC and FAP maintained higher levels of starch arid respiration as compared to control plants at three stages of samplings.